Pengertian Pemimpin dan Kepemimpinan, Dimensi, Teori Kepemimpinan - Kartika , Ika; Jamlaudin , Gagan; Latipatinupus; Maenatul M, Rina (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Leaders and leadership have been an inseparable part of human nature since the beginning of their existence. The discussion of leaders and leadership not only explains the characteristics and abilities needed to be an effective leader, but also highlights their strategic role in driving the organization and achieving common goals. A popular saying states that no country or organization can survive without adequate leaders. This confirms that leaders are the essence of management, and the success of an organization is greatly influenced by the morality and competence of its leaders. However, not all individuals who occupy leadership positions have the appropriate abilities or even a deep understanding of the essence of leadership. Conversely, many have a natural talent for leadership but never get the opportunity to explore their full potential. Rasulullah SAW. is considered a prime example in terms of leadership, spreading goodness and beauty in life. In the educational context, leadership plays an important role in organizing educational institutions. Even in a smaller scope, teachers must have a leadership spirit to manage the class, organize learning well, and motivate students. Leadership itself can be defined as the process of influencing and directing group activities towards a common goal, involving strategy, commitment and development of organizational culture. Leadership theory can be categorized into 4 parts, namely (1) Great Man Theory and Big Bang Theory, (2) Theory of Personality Traits (Characteristics), (3) Behavioral Theories (4). Contingency Theory or Situational Theory. In conclusion, leaders and leadership play a crucial role in every aspect of human life, from organizations to education. Effective leader development requires a deep understanding of leadership theories and the application of leadership values ​​in everyday life.